Association of the load-velocity relationship variables with 2000-m rowing ergometer performance - Pérez-Castilla, A.; Leandro Quidel-Catrilelbún, M. E.; Rodriguez-Perez, M. A.; García-Ramos, A. (European Journal of Sport Science, 2023)
This study aimed to compare the maximal mechanical variables derived from the load-velocity (L-V) relationship and 2000-meter rowing ergometer performance between rowers of different age categories, and to identify the L-V relationship variables more closely related to 2000-meter rowing ergometer performance. Nineteen competitive rowers (15 males and four females) aged between 15 and 25 years were evaluated during the national 2000-meter rowing ergometer competition organised by the Chilean Rowing Federation. Thereafter, the L-V relationship variables (load-axis intercept [L0], velocity-axis intercept [v0], and area under the L-V relationship line [Aline]) were determined on separate occasions during the squat jump and prone bench pull exercises. Rowers were classified according to their chronological age for comparative purposes (under 16 years [U16] vs. over 16 years [O16]). L0 and Aline were always higher for O16 than for U16 (p = 0.046; ES range = 0.99-1.79), while v0 was generally comparable for both age categories (p = 0.038; ES range = 0.07-1.03). Furthermore, the O16 revealed a greater performance (i.e. shorter total time) during the 2000-meter rowing ergometer competition (p = 0.011; ES = -1.31). In general, significant correlations were obtained between rowing performance and the L-V relationship variables obtained during the squat jump (r or Rho range = -0.294 to -0.922) and prone bench pull (r or Rho range = -0.322 to -0.928). These results support the L-V relationship as a sensitive procedure to evaluate the maximal mechanical capacities of lower- and upper-body muscles in competitive rowers.